2011
DOI: 10.1160/th10-10-0662
|View full text |Cite
|
Sign up to set email alerts
|

CC and CXC chemokines are pivotal mediators of cerebral injury in ischaemic stroke

Abstract: The definition of ischaemic stroke has been recently updated as an acute episode of neurological dysfunction caused by focal brain, spinal cord, or retinal ischaemia in the presence of a cerebral infarction. This "tissular" definition has highlighted the importance of pathophysiological processes underlying cerebral damage. In particular, post- ischaemic inflammation in the brain and in the blood stream could influence crucial steps of the tissue injury/repair cascade. CC and CXC chemokines orchestrate the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(46 citation statements)
references
References 135 publications
(180 reference statements)
0
46
0
Order By: Relevance
“…8,9 Chemokines and their cognate receptors regulate both physiological and pathological processes in the central nervous system, and it is currently postulated that chemokines play a generally deleterious role by contributing to brain injury after cerebral ischemia-reperfusion. 10 We have shown that expression of numerous chemokinerelated genes is upregulated in the mouse brain from 4 hours for ≥3 days after ischemia-reperfusion, 11 raising the possibility that certain key chemokines/chemokine receptors could represent targets for acute stroke therapy. For example, we 538 Stroke…”
mentioning
confidence: 98%
“…8,9 Chemokines and their cognate receptors regulate both physiological and pathological processes in the central nervous system, and it is currently postulated that chemokines play a generally deleterious role by contributing to brain injury after cerebral ischemia-reperfusion. 10 We have shown that expression of numerous chemokinerelated genes is upregulated in the mouse brain from 4 hours for ≥3 days after ischemia-reperfusion, 11 raising the possibility that certain key chemokines/chemokine receptors could represent targets for acute stroke therapy. For example, we 538 Stroke…”
mentioning
confidence: 98%
“…Similar reductions in chemotaxis were also noted for monocytes, macrophages, and monocyte-derived dendritic cells toward their cognate ligands in the presence of MVC (0.1–10 μM) [12]. These intrinsic immunomodulatory effects associated with CCR5 antagonism are highly desirable for the treatment of inflammatory and autoimmune conditions including graft-versus-host disease [13], multiple sclerosis [14], and ischemic stroke [15]. However, CCR5 has also been heavily implicated in the development of CD8 + T cells [1618] which play a critical role in the clearance of virus-infected cells and in the pathogenesis of HIV infection [19,20].…”
Section: Ccr5 Biology and Chemokine Receptor-based Hiv Tropismmentioning
confidence: 80%
“…There are not enough studies considering levels of CXCL9 in stroke; however, it is known to be involved in inflammatory disorders such as atherosclerosis and rheumatoid arthritis, and participation with other inflammatory factors is well studied [3,12,14,19,20]. Its beneficial role in muscle reconstruction along with other chemokines is also well known [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…They are also functionally described as "homeostatic" (meaning that they are secreted constitutively and involved in immune surveillance and mostly lymphocyte traffic) or "inflammatory" (meaning that they mediate pro-inflammatory signals and induce leukocyteoriented locomotion to the damaged or infected tissue). Chemokines have also been shown to influence the phenomena of angiogenesis and cellular differentiation [12].…”
Section: Introductionmentioning
confidence: 99%